A serious game design framework for vocabulary learning of children with autism / Kamran Khowaja - Kamran, Khowaja (2017)
The use of serious games to provide intervention of different skills related to autism has increased in recent years. However, the potential of serious games to provide intervention of vocabulary to autistic children has been underutilised despite its importance in the overall reading comprehension. The task to design serious games for vocabulary learning of these children becomes more challenging as there are no existing serious game design frameworks (SGDFs) to provide guidance throughout the design process. The framework and its components play a vital role as it spells out what needs to be incorporated into the serious games. The main aim of this research is to construct an SGDF to design serious games for these children to learn vocabulary. First, the components related to children with autism and serious games that could constitute a serious-game design were identified from the extensive review of literature on autism and existing SGDFs. Second, the identified components were logically grouped within intra-frameworks and then across the inter-frameworks. An input, process and output (IPO) model was selected as an underlying structure to construct the framework. The components resulting from the intra- and inter-frameworks grouping were logically placed into the phases of IPO model to produce the initial version of the framework. The expert reviews were conducted in an iterative manner for the evaluation of framework from the perspective of academicians and researchers working in the area of serious games, and game designers. An applicability validation was also conducted to assess the application of the framework. The framework was modified and revised version of the framework was produced based on the outcomes of all the evaluations. Third, a serious game design was produced and design was transformed into a serious game prototype to show the logical view of the proposed framework. Fourth, a heuristic evaluation was performed on the prototype using the modified set of heuristics developed as part of this research to improve its overall usability. An experimental evaluation of the prototype was conducted using single-subject research design to measure the performance in learning vocabulary among autistic children before and after using the prototype. The main finding from expert reviews shows that structure, components and their details of the proposed framework have been effectively refined. The hands-on experience of experts working with framework for its applicability positively reaffirms its practical use. The visual analyses of experimental evaluation of the prototype revealed that the receptive identification based on the average number of correct answers selected by these children across the sessions improved from the baseline (53.97%) to intervention (92.57%) and maintenance (93.73%). It also revealed that the average number of attempts made to identify correct answers across the sessions of each child lowered from baseline (1.9) to intervention (1.1) and maintenance (1.1). The results will help researchers and game designers to design serious games for these children, develop prototypes, and perform its usability evaluation.